2010
DOI: 10.1108/17506161011047398
|View full text |Cite
|
Sign up to set email alerts
|

Market orientation, job satisfaction, commitment and organisational performance

Abstract: Purpose -The purpose of this paper is to analyse the implementation of the marketing concept within both the internal (internal market) and external environments in the context of the local public sector. It also aims to examine the impact of market orientation (MO) on employees' job-related attitudes ( job satisfaction and organisational commitment (OC)) and organisational performance (OP). Design/methodology/approach -Researchers take a methodological approach by using a survey method. Structural equation mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 60 publications
(76 reference statements)
5
48
0
1
Order By: Relevance
“…This finding is consistent with previous studies in both the for-profit (Siguaw et al 1994) and the non-profit contexts (Rodrigues and Pinho 2010;Caruana et al 1999). …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is consistent with previous studies in both the for-profit (Siguaw et al 1994) and the non-profit contexts (Rodrigues and Pinho 2010;Caruana et al 1999). …”
Section: Discussionsupporting
confidence: 93%
“…In relation to measuring organisational commitment from the perspective of managers, we follow the same approach as the classic work of Jaworski and Kohli (1993) as well as of other authors (Rodrigues and Pinho, 2010;Lok and Crawford, 2004;Rashid et al, 2003).…”
Section: < Table 1: Construct Definition and Operationalisation >mentioning
confidence: 99%
See 1 more Smart Citation
“…This shows these African countries are all a head of Nigeria interms of performance and satisfaction with the quality of education in their respective nation (WorldBank, 2010). Despite the fact that Nigeria serve as the most populous country in the continent and the third country interms economic growth after S/Africa and Egypt respectively (WorldBank., 2010), While this sector remained the back born of any country economy as well as development (Aluede, Idogho, & Imonikhe, 2012;WorldBank., 2013;http://dx.doi.org/10.15405/epsbs.2018.05.42 Corresponding Author: Malam Salihu Sabiu Selection and peer-review under Previous studies were conducted to identified some factors that influence OP, for example, organizational learning (Barba-Aragón, Jiménez-Jiménez, & Sanz-Valle, 2014;Garcia-Morales et al, 2012;Jiménez-Jiménez & Sanz-Valle, 2011;López, Peón, & Ordás, 2005;Tippins & Sohi, 2003), commitment (Ali, Rehman, & Ali, 2010;Pinho et al, 2014;Rodrigues & Pinho, 2010), quality management practices (Appiah-Fening, Pesakovic, & Amaria, 2008;Fening, 2012;Phan, Abdallah, & Matsui, 2011), organizational support (Hau-siu, Lo, Sha, & Hong, 2006Joiner, 2007), environment (Chandrasekar, 2011;Cosh, Fu, & Hughes, 2012). Others investigated the influence of interpersonal trust (Bakiev, 2013;Paul & Mcdaniel, 2004), personality (Barrick, Mount, & Judge, 2001;Soane, Butler, & Stanton, 2015), attitudes (Gregory et al, 2009; among others.…”
Section: Problem Statementmentioning
confidence: 99%
“…Thang (2004) argued that compensation and reward can be influential tools for attaining efforts from the personnel to fulfill the organizational objectives. In Malaysian context compensation is an important practice that increase job satisfaction (Jauhar et al, 2015) and job satisfaction leads to organizational performance (Rodrigues & Carlos M, 2010;Yousef, 2000). According to expectancy theory of Vroom (1964), reward is a form of direct and indirect compensation packages and it has potential to influence employee work motivation.…”
Section: Compensationmentioning
confidence: 99%